2022
DOI: 10.3389/fmicb.2022.960728
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol inhibits biofilm formation of methicillin-resistant Staphylococcus aureus and increase the therapeutic effect of vancomycin in vivo

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is among the common drug resistant bacteria, which has gained worldwide attention due to its high drug resistance and infection rates. Biofilms produced by S. aureus are known to increase antibiotic resistance, making the treatment of S. aureus infections even more challenging. Hence, inhibition of biofilm formation has become an alternative strategy for controlling persistent infections. In this study, we evaluated the efficacy of geraniol as a treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Aside from QS system, the SarA regulatory system is also involved in the regulation of biofilm formation ( 43 ). The role of SarA regarding biofilm formation is to repress the production of extracellular proteases and PIA, and induce the expression of fnbA , fnbB , and clfA (determinants of S. aureus surface adhesins) ( 44 ). In our study, we found that exposure to sub-inhibitory concentrations of S-342-3 resulted in a reduction in the expression of the regulatory gene sarA .…”
Section: Discussionmentioning
confidence: 99%
“…Aside from QS system, the SarA regulatory system is also involved in the regulation of biofilm formation ( 43 ). The role of SarA regarding biofilm formation is to repress the production of extracellular proteases and PIA, and induce the expression of fnbA , fnbB , and clfA (determinants of S. aureus surface adhesins) ( 44 ). In our study, we found that exposure to sub-inhibitory concentrations of S-342-3 resulted in a reduction in the expression of the regulatory gene sarA .…”
Section: Discussionmentioning
confidence: 99%
“…For antibiofilm formation activity, geraniol and camphor exhibited antibiofilm activity by inhibiting S. aureus biofilm with the inhibition percentage of 86.13 ± 5.22 and 81.25 ± 1.63 after exposure to 256 µ g/mL of geraniol and 10 mg/mL of camphor, respectively [ 41 , 42 ]. Furthermore, Vijayakumar et al [ 43 ] found that eucalyptol showed a concentration-dependent manner for inhibition of biofilm formation of Streptococcus pyogenes by 89% inhibition after exposure to this chemical at a concentration of 300 µ g/mL.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in accordance with previous reports that many natural compounds were able to destroy the structure of biofilm. For instance, Gu et al (2022) observed the biofilm of S. aureus USA300 on slides decreased as the concentration of geraniol increased. The morphological changes of S. aureus biofilm treated with punicalagin was also confirmed by CLSM.…”
Section: Discussionmentioning
confidence: 99%